Peran Keluarga dalam Asuhan Keperawatan Dan Pemenuhan Gizi Pada Balita Malnutrisi - Cut Salsabila Alya Zahra; Dinasti Pudang Binoriang (Universitas Pahlawan Tuanku Tambusai, 2026)
Malnutrition remains a significant health problem in toddlers because it can affect physical growth, cognitive development, and overall health. Parents play a crucial role in meeting nutritional needs, but often face obstacles due to limited knowledge, inappropriate feeding practices, and environmental conditions. This study aims to explore and strengthen parental involvement in toddler nutrition management through a family-based intervention. The study used a case study approach with one toddler who was underweight and stunted. Data were collected through anthropometric measurements, in-depth interviews with the mother, and observations of feeding practices at home. The intervention was implemented for one month with four weekly visits and included nutrition education, demonstrations of feeding practices, counseling, and growth monitoring. The evaluation showed an increase in parental knowledge, attitudes, and practices in child nutrition management, as well as improvements in the toddler's nutritional status. These results indicate that family-based interventions can empower parents, improve nutrition practices, and support optimal growth and development of toddlers.